The effect of antithrombotic drug use on delayed bleeding with esophageal endoscopic resection. Issue 9 (25th July 2022) - Horie, Yoshimasa; Horiuchi, Yusuke; Ishiyama, Akiyoshi; Tsuchida, Tomohiro; Yoshimizu, Shoichi; Hirasawa, Toshiaki; Fujisaki, Junko; Maetani, Iruru; Yoshio, Toshiyuki
Abstract: Background and Aim: Whether antithrombotic drugs increase the risk of post‐esophageal endoscopic resection bleeding is unknown. This study examined the effect of antithrombotic drugs, aspirin, thienopyridine, direct oral anticoagulants (DOAC), and warfarin, on post‐esophageal endoscopic resection bleeding. Methods: We enrolled 957 patients (1202 esophageal tumors) treated with endoscopic resection and classified them based on antithrombotic drug use as no use, aspirin, thienopyridine, DOAC, and warfarin . Patients using antiplatelet drugs (i.e. aspirin and thienopyridine) were further sub‐classified based on their continued or discontinued use before endoscopic resection. The bleeding rates were compared between these groups to assess the effects of antithrombotic drug use and interruption of antiplatelet therapy on post‐esophageal endoscopic resection bleeding. Results: The post‐endoscopic resection bleeding rate was 0.3% (95% CI, 0.1–1) in the group without antithrombotic drug use, 4.5% (95% CI, 0.1–23) in the aspirin‐continued group, 2.9% (95% CI, 0.1–15) in the aspirin‐discontinued group, 0% (95% CI, 0–78) in the replaced thienopyridine with aspirin group, 0% (95% CI, 0–26) in the thienopyridine‐discontinued group, 13% (95% CI, 1.6–38) in the DOAC group, and 0% (95% CI, 0–45) in the warfarin group. The post‐endoscopic resection bleeding rate in the DOAC group was significantly higher than that in the group without antithrombotic drugs ( P = 0.003). The post‐endoscopic resection bleeding rates did not differ between the other groups. Conclusions: Our results suggest that discontinuing aspirin is not necessary for esophageal endoscopic resection while we must be careful regarding DOAC.